2012
DOI: 10.1186/1465-9921-13-68
|View full text |Cite
|
Sign up to set email alerts
|

L-citrulline supplementation reverses the impaired airway relaxation in neonatal rats exposed to hyperoxia

Abstract: BackgroundHyperoxia is shown to impair airway relaxation via limiting L-arginine bioavailability to nitric oxide synthase (NOS) and reducing NO production as a consequence. L-arginine can also be synthesized by L-citrulline recycling. The role of L-citrulline supplementation was investigated in the reversing of hyperoxia-induced impaired relaxation of rat tracheal smooth muscle (TSM).MethodsElectrical field stimulation (EFS, 2–20 V)-induced relaxation was measured under in vitro conditions in preconstricted tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…− overproduction. Ramadan and co-workers demonstrated that the presence of an L-citrulline/L-arginine cycle in the airways of rat pups and L-citrulline supplementation reversed the impaired relaxation of airways under hyperoxic conditions 24 . Ananthakrishnan and associates indicated that L-citrulline supplementation ameliorated the development of pulmonary hypertension and increased NO production in piglets exposed to chronic hypoxia 25 .…”
Section: Discussionmentioning
confidence: 99%
“…− overproduction. Ramadan and co-workers demonstrated that the presence of an L-citrulline/L-arginine cycle in the airways of rat pups and L-citrulline supplementation reversed the impaired relaxation of airways under hyperoxic conditions 24 . Ananthakrishnan and associates indicated that L-citrulline supplementation ameliorated the development of pulmonary hypertension and increased NO production in piglets exposed to chronic hypoxia 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental inhaled NO (iNO) also ameliorates the BPD phenotype in experimental models and in some premature infants. Lung parenchymal NO-mediated relaxation is impaired in rat neonates exposed to hyperoxia ( Sopi et al, 2007 ), which could be restored by inhibition of the increased arginase activity ( Ali et al, 2012 ), or with supplementation with L -arginine ( Ali et al, 2012 ) or L -citrulline ( Sopi et al, 2012 ). L -Citrulline supplementation prevents hyperoxia-induced lung injury and PH in newborn rats ( Vadivel et al, 2010 ).…”
Section: Increasing Arginine Availabilitymentioning
confidence: 99%
“…Pups were exposed to neonatal hyperoxia starting at age P5 which represent the transition day from saccular to alveolar phase of lung development in rats (O'Reilly & Thebaud, 2014). The 5th day of life, as starting point for exposure to oxygen might not be critical to induce strong structural changes in the airways and interstitial parenchyma of lungs to represent remodeling, but it is critical day to induce functional changes in respiratory system, particularly to trigger airway hyperreactivity that was proven in our previous publications (Sopi et al, 2007(Sopi et al, , 2012. Lungs at this age are immature, which is one of the risk factors of BPD (Speer, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…The trachea was removed and prepared free of serosal connective tissue in an ice-cold oxygenated Krebs-Henseleit (KH) buffer (concentration in mM: 118.2 NaCl, 25 NaHCO 3 , 4.6 KCl, 1.2 KH 2 PO 4 , 1.2 MgSO 4 , 2.5 CaCl 2, and 10% D-glucose, pH = 7.4; all obtained from Sigma-Aldrich). Two cylindrical airway segments of 3-mm length were isolated from the midportions of the tracheas for each animal, and transferred into a tissue-organ bath containing KH buffer (10 ml) at 37°C, as previously described (Sopi et al, 2012).…”
Section: In Vitro Measurement Of Contraction and Relaxation Of Tsmmentioning
confidence: 99%